1108. Transplantation and Immigration: Comparing Infectious Complications Between Foreign-born vs. U.S.-born Kidney Transplant Recipients in Minnesota - Espinoza, Eloy E Ordaya (Open Forum Infect Dis, 2020)
BACKGROUND: Immigrant patients face barriers to kidney transplantation due to language, cultural, and economic issues. Unprepared health systems and providers further contribute to health disparities in transplantation. Foreign-born patients are also at risk for reactivation of latent infections which differ from U.S.-born population. Stratifying transplant recipients according to country of birth could guide clinicians in the prevention, anticipation, diagnostics, and treatment of post-transplant infections. METHODS: A retrospective, observational, multicenter study of patients that underwent kidney transplantation from 1/2014-12/2018 at the University of Minnesota Medical Center and Hennepin Healthcare is being conducted. Sociodemographic, clinical, and laboratory data are collected, including infectious episodes during the first year post-transplant. RESULTS: One-hundred patients are included in this preliminary analysis (recruitment goal is 800 patients). Sixty-five patients were males (65%), with median age 56 years (range 20 – 77). The majority were Caucasians (64%), followed by Asians (12%) and Africans (9%). Living donation was 59%. Seventy-eight patients developed infectious complications during the first year after transplantation, for a total of 175 infectious episodes: viral etiology (51%), followed by bacterial (42%) and fungal (7%). No tropical diseases were found. Comparing foreign-born (30%) vs. U.S.-born (70%), foreign-born recipients had a higher frequency of latent tuberculosis infection (LTBI) (37% vs 1%, p< 0.001), hepatitis B core antibody positive (20% vs 0, p< 0.001), and deceased donor transplant (67% vs 30%, p= 0.001). CMV mismatch (3% vs 36%, p= 0.002) was more frequent in U.S.-born recipients; CMV reactivation was similar in both groups. While not statistically significant, more foreign-born recipients had an infection in the first year post-transplant (90% vs 73%, p= 0.1), and higher median infectious episodes (2 vs 1, p= 0.6). Comparison of foreign-born vs U.S.-born kidney transplant recipients (n=100, preliminary data) [Image: see text] CONCLUSION: Per this preliminary data, foreign-born transplant recipients had a higher frequency of LTBI, hepatitis B core antibody and infectious complications, but lower frequency of CMV mismatch. No cases of tuberculosis, hepatitis B reactivation or tropical diseases were observed. DISCLOSURES: Patricia F. Walker, MD, DTM&H, FASTMH, UpToDate (Other Financial or Material Support, Royalties from UpToDate for chapter on refugee screening)